The effectiveness of urban policies facing spatial polarization - Oliver Thomas (European Regional Science Association (ERSA), 1998)
This paper intends to find whether cities can significantly exert an influence on their future and partly break away from the constraints with which they have to cope. The ability of key-actors, in charge of urban development, to solve the difficulties and the various urban uncertainties which are thwarting urban growth will consequently be analysed. First the means available for strategic urban plans will be pointed out as specific tools in order to reduce urban uncertainties, such as the growth rate of taxes for firms and households, or the thorny task of attracting and anchoring productive activities for instance. Therefore, contractual urban policies, the non-fulfilment and the indecisiveness of which entail the recourse to conventional tools, will provide urban actors with a special kind of spatial insurance. This latter will be stressed as the main result of such metropolitan policies. Thus the two major shapes that this insurance may take will be detailed in the second part of this paper : the first one (assurantial) will convey the advantage to dispose of a large number of heterogeneous people so that the various potential risks may be easily tackled. The second one (organizational) will underline the "internal" solutions to deal with such risks that local cooperations and synergies (within a city) may embody. Dividing risks or cooperating to face them : this manichean dilemma will be challenged, considering the results of an econometric analysis hinting that both exogeneous and endogeneous patterns may exert an influence in uncertainties lessening, and accordingly in urban growth enhancing. This will finally lead us to highlight the specific context in which urban policies are embedded, defining it merely with two facets : the diminution of the strategic importance of transportation costs compared with sunk costs, and the existence of economies of scale. Therefore, the misleading relevance of public policies making people and information movements easier will be raised. Urban policies, however exerting sometimes an unvoluntary enhancing of spatial polarization, will nevertheless emerge as useful (though partial) tools, which will underline above all the leading influence of the acuteness of urban elites.
Keywords: 330